THE700: Thesis / College of Creative Arts - UiTM, College of Creative Arts (2023)
This course consists of two components of delivery; (a) Theoretical Research and (b) Practiced-Based Research. The Theoretical Research is focused on enroll in particular programme. Students will select the appropriate research approach such as comparative, descriptive, experimental, historical and practical research to conduct a research project and produce a research dissertation. The Practice Based Research encompasses practical approaches in developing and producing an art and design project. Such approaches are dealt with and analyzed in the process of producing art and design work. This development will involve researching, developing, resolving and reflecting processes. Students will be able to use these approaches to produce art/design works with relevant concepts and publish project reports/ artist statements.